Server-side GPS and assisted-GPS in Java - Harper, Neil (GNSS technology and applications series., 2010)
Assisted GPS (A-GPS) is a technology that greatly enhances GPS performance and capabilities. This innovative book offers you a detailed explanation of the way that an A-GPS server operates from a practical point of view. You learn how A-GPS improves critical aspects of GPS, such as time-to-first-fix (TTFF) and yield. The book focuses on handset-assisted A-GPS, where the server can make use of additional information and perform more effective hybrid calculations. You gain insight into factors affecting accuracy and how these errors can be minimized using A-GPS. Moreover, this unique resource includes example code in Java for all key functions, along with sequence diagrams in UML that help ensure a solid understanding of the material. CD-ROM Included! Contains valuable Java source code and example applications that illustrate key points throughout the text. Complete class and sequence diagrams are also provided where applicable.